Evaluasi pengetahuan remaja dan partisipasinya pada kegiatan Pelayanan Kesehatan Peduli Remaja (PKPR) - Idha Farahdiba; Noviyani Hartuti (Holistik Jurnal Kesehatan, 2021)
Youth Care Health Program (YCHP) among adolescent students: Knowledge and participation Background: Teenagers can access the health center to get some information regarding health and consultation with their psychological problems. Youth Care Health Program (YCHP) focuses more on promotive and preventive services, considering that adolescence is a time when problems are caused by ignorance, misperception, and lack of consideration in acting and preventing destructive behavior.Purpose: To evaluate adolescent knowledge of adolescent knowledge with adolescent participation in the Youth Care Health Program (YCHP).Method: The research method used is the Cross Sectional Study method. The population of the study was teenagers who had attended the Youth Youth Care Health in the working area of the Dahlia Health Center, Makassar City. The sampling technique used purposive sampling technique obtained 42 participants. The research instrument used a questionnaire to assess adolescent knowledge and youth participation by observing their presence, activeness, and enthusiasm in Youth Care Health Program (YCHP). The analytical technique is used in univariate and bivariate data analysis (chi-square test). α-value = 0.05Results: The adolescents with a good knowledge 36 (85.7%) and has a high desire participation of 31 (73.8%). The correlation of all variables independent with participation as dependent variable was >0.05Conclusion: There was not a relationship between Youth Care Health Program (YCHP) among adolescent in knowledge and participation.Keywords: Adolescent; Knowledge; Participation; Youth Care Health Program (YCHP).Pendahuluan: Remaja dapat mengakses layanan dengan mudah hanya datang ke puskesmas yang telah ditunjuk untuk menyelenggarakan program tersebut. PKPR lebih berfokus pada pelayanan promotif dan preventif dimana mengingat masa remaja merupakan masa dimana permasalahan disebabkan oleh ketidaktahuan, salah persepsi, hingga kurangnya pertimbangan dalam bertindak. ketidaktahuan remaja tentang layanan PKPR merupakan faktor penting dalam menentukan akses PKPR oleh remaja.Tujuan: Diketahui apakah terdapat hubungan pengetahuan remaja terhadap partisipasi remaja dalam kegiatan PKPR.Metode: Menggunakan metode Cross Sectional Study dengan populasinya penelitian remaja yang pernah mengikuti posyandu remaja di wilayah kerja Puskesmas Dahlia Kota Makassar. Teknik pengambilan Sampel menggunakan teknik purposive sampling didapatkan sampel berjumlah 42 responden. Instrumen penelitian menggunakan kuisioner untuk menilai pengetahuan remaja dan partisipasi remaja dengan mengobsevasi kehadiran, keaktifan dan antusiasnya selama kegiatan PKPR. Teknik analisa menggunakan analisis data univariat dan bivariat (uji chi-square) dengan nilai α sebesar 0,05.Hasil: Remaja dengan pengetahuan baik 36 (85,7%) dan memiliki keinginan partisipasi tinggi sebesar 31 (73,8%). Korelasi semua variabel independen dengan partisipasi sebagai variabel dependen adalah >0,05Simpulan: Penelitian didapatkan bahwa tidak ada hubungan antara pengetahuan remaja tentang PKPR dengan partisipasi remaja dalam kegiatan PKPR.